Design Of The Indonesian Film Museum - Afifah Anzila Syahriani Ramadhan; Nutrian Galupamudia; Kemal Affandi (Publikasi Indonesia, 2024)
The increasing public interest in Indonesian cinema accompanied by a lack of insight into the history and development of film technology, as well as the absence of museums that highlight this theme, are challenges that need to be overcome. This research aims to design the Indonesian Film Museum as a forum for education and information about the history and technology of film, so that people can get to know and appreciate local works better. The method used is qualitative with a descriptive approach. The research population consists of people who are interested in film, with a sample of 30 respondents taken purposively through interviews and observation. Data collection includes literature study, in-depth interviews, and field observations. Data analysis is carried out by organizing, classifying and interpreting the data obtained. The research results show that the design of the Indonesian Film Museum can meet educational needs related to film history, equipped with facilities such as exhibition rooms, workshops and a mini cinema. This museum is expected to attract visitor interest and function as a film information center. The conclusion of this research states that the design of the Indonesian Film Museum can make a positive contribution to the development of the film industry and increase public knowledge about the history of film in Indonesia. Previous research, such as that conducted by Angkirawan (2017) and Nugroho (2020), highlighted the importance of developing museums as a means of education and preserving film history. The theoretical framework focuses on thematic architectural concepts and the role of museums in society as educational centers that offer interesting learning experiences for visitors.